Temporomandibular disorders in an adult population in northern Norway: A cross‐sectional study - Elin Hadler‐Olsen; Elizabeth Thon; Gro Eirin Holde; Birgitta Jönsson; Nils Oscarson; Anders Tillberg (Wiley, 2021)
Abstract Objectives The aim of the study was to assess the prevalence of symptoms indicative of temporomandibular disorders (TMD) in an adult population in Troms County in Northern Norway, as well as the associations between TMD and socio‐demographic factors, dental status, self‐reported general, and oral health as well as oral health related quality of life (OHQoL). Methods Data were collected from a structured questionnaire and a clinical examination of a random sample of almost 2000 adults, 20-79‐year‐old, in Troms County in Northern Norway. Results Women had a higher prevalence of all self‐reported and clinical signs of pain and dysfunction in the temporomandibular complex compared to men. For both genders, sounds from the temporomandibular joint (TMJ) upon clinical examination was the most common symptom, followed by pain to palpation of jaw muscles. Headache was the most common of the self‐reported symptoms and sounds from the TMJ the second most common. Young women had a higher prevalence of self‐reported headache and jaw‐ and face pain compared to middle‐aged and elderly women. TMD‐related symptoms of pain were significantly associated with poor self‐reported general health and correlated with OHQoL as assessed by the oral health impact profile 14 questionnaire. Conclusion Being women and having moderate to poor self‐reported general health were associated with clinical signs and self‐reported symptoms of pain in the jaw, face and head region. Self‐reported symptoms of TMD correlated more strongly with OHQoL than clinical signs.